2013
DOI: 10.3109/11038128.2013.785017
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perceptions of occupational competence among participants in Individual Placement and Support (IPS)

Abstract: Beyond those occupations valued as most important among the participants, it is essential also to pay attention to those in which they perceived least competence, as they are important for being able to achieve a desired occupation. Support related to perceptions of occupational competence can contribute to enabling clients in IPS to master a desired working life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…The concept that engaging in the IPS programme does not happen in isolation has only been illustrated by two other studies (Nygren et al, 2013;Siu et al, 2010). Sui et al (2010) found that after steady employment for 3 months, participants perceived a positive impact on wellbeing in terms of quality of life and financial satisfaction, but also found negative impacts such as physical and psychological exhaustion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept that engaging in the IPS programme does not happen in isolation has only been illustrated by two other studies (Nygren et al, 2013;Siu et al, 2010). Sui et al (2010) found that after steady employment for 3 months, participants perceived a positive impact on wellbeing in terms of quality of life and financial satisfaction, but also found negative impacts such as physical and psychological exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were limited by the participants' ability to recall experiences pre-employment and the effect of medication on memory and recall. The reciprocal effect is highlighted by Nygren et al (2013), who underlined the relationship between the consumer's perceptions of their occupational performance in nonvocational areas, and their engagement and progression in the IPS programme. This study emphasized the need for additional support in non-vocational areas, and in balancing the demands of work and other aspects of their lives, to enable clients to achieve and sustain employment (Nygren et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational competence and occupational value were assessed by using the Occupational Self Assessment (OSA), and the Swedish version (1.0) of the OSA was used (Baron et al 1998, Hellsvik 2000Nygren et al 2013). OSA is a self-report instrument where the person responds to 21 statements by indicating his or her perceptions of how well he or she performs everyday occupational behaviours (occupational competence) and how important these occupational behaviours are for the person (occupational value).…”
Section: Documentation Performed By the Ips Coachesmentioning
confidence: 99%
“…Basic statistics were used to analyze the outcome of four of the five instruments used in the study (Nygren et al 2011) and Rasch analyses were used for the OSA (Nygren et al 2013). Median values for all five quantitative instruments (BPRS, Rosenberg, MANSA, GAF, OSA), and for the frequency of IPS provided, were calculated for the whole group of participants at baseline (n = 65) and at the 24-month follow-up (n = 45).…”
Section: Statistics and Analysesmentioning
confidence: 99%